Refractory and relapsing forms of Clostridium difficile-associated colitis - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss the factors promoting development of refractory and relapsing forms of colitis, associated to Clostridium difficile infection, to present the state-of-the-art in management of patients with these variants of the course of disease.Original positions. Relapsing forms of the Clostridium difficile-associated colitis, are seen in 15– 30% of patients. Their development is promoted by elderly age of patients, significant duration of diarrhea at the first relapse, intake of proton pump inhibitors. In treatment of such patients courses of vancomycine and metronidazole, supplemented by probiotics (Sacharomyces boulardi), adsorbents (Colestyraminum, smecta) and rifaximin are applied.Conclusion. The problem of refractory and relapsing forms of Clostridium difficile-associated colitis, requires the further studying to increase treatment efficacy.